Empirical aspects of unemployment in Barbados - Craigwell, Roland C. ([Caribbean Centre for Money & Finance] St. Augustine]TT, 1998)
Discusses features of the labour market and develops an econometric model to examine the causes of unemployment in Barbados. Examines also, the various labour market policies adopted by government and other agencies to reduce unemployment.